2019
DOI: 10.2174/1871530318666181022164505
|View full text |Cite
|
Sign up to set email alerts
|

The Epithelial Barrier Model Shows That the Properties of VSL#3 Depend from Where it is Manufactured

Abstract: Background: VSL#3 has been extensively investigated and is currently recommended for the prevention and treatment of chronic pouchitis and ulcerative colitis. Nonetheless, in vitro and in vivo studies have recently shown variability in the VSL#3 efficacy often attributed to the manufacturing process. Objective: The aim was to comparatively study the in vitro effects of two VSL#3 preparations produced in different sites (named US- and Italy-made VSL#3) on CaCo-2 epithelial barrier model in terms of trans-epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The specific mechanisms of action underlying the benefits of a probiotic treatment other than the normalization of perturbed intestinal microbiota communities also include direct effects on intestinal epithelial mucosa and modulation of the immune system [46][47][48]. Of interest, through in vitro models the direct beneficial effects of selected probiotics on damaged intestinal epithelial barrier have been recently reported by our group [49,50]. In this context, it may be useful to investigate the effect of appropriate probiotic administration on intestinal barrier function other than the dysbiosis level in SNAS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The specific mechanisms of action underlying the benefits of a probiotic treatment other than the normalization of perturbed intestinal microbiota communities also include direct effects on intestinal epithelial mucosa and modulation of the immune system [46][47][48]. Of interest, through in vitro models the direct beneficial effects of selected probiotics on damaged intestinal epithelial barrier have been recently reported by our group [49,50]. In this context, it may be useful to investigate the effect of appropriate probiotic administration on intestinal barrier function other than the dysbiosis level in SNAS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in the light of a number of recent scientific reports [55][56][57][58][59][60][61], changes in the manufacturing processes, equipment, or facilities, which could result in detrimental differences in the final probiotic product, should be strictly controlled in terms of safety and efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Grześkowiak studied several L. rhamnosus GG isolates from different probiotic products and confirmed that some beneficial properties were lost depending on the manufacturing site, notwithstanding the genetic identity of the strains tested [3]. Recently, some publications also discussed the equivalence of the VSL#3 probiotic formulation produced in two different manufacturing facilities [4][5][6].…”
Section: Introductionmentioning
confidence: 87%
“…Despite that VSL#3 strains were reported with different names in the two products and the relative concentrations of the eight strains components were not given, Italian and American products were commercialized under the same brand and the producer did not declare any difference in composition between them. Hence, as in previous works [4][5][6], we considered the two products as having identical formulation.…”
Section: Introductionmentioning
confidence: 99%